+0  
 
0
377
2
avatar+603 

make "p" the subject.

 

\(x={5 \over3}- \sqrt{2p-1}\)

 

I did this:

 

\({3 \over5}x=- \sqrt{2p-1} \)

 

\(({3\over5}x)^2 = -2p-1\)

 

\(\)\(({3\over5}x)^2 + 1 = -2p\)

 

\({9 \over25}x^2 + 1 = -2p\)

 

\({34 \over25}x^2 = -2p\)

 

\(-{1 \over2}*{34 \over25}x^2 = p\)

 

\(-{17 \over25}x^2 = p\)

 

Is this correct?...Thank you for your time...

 Nov 12, 2018
edited by juriemagic  Nov 12, 2018

Best Answer 

 #1
avatar+24093 
+10

make "p" the subject.
\(\displaystyle x={5 \over3}- \sqrt{2p-1}\)

 

\(\begin{array}{|rcll|} \hline x &=& \dfrac{5}{3} - \sqrt{2p-1} \quad & | \quad -\dfrac{5}{3} \\ x-\dfrac{5}{3} &=& - \sqrt{2p-1} \quad & | \quad \times(-1) \\ -x+\dfrac{5}{3} &=& \sqrt{2p-1} \\ \dfrac{5}{3}-x &=& \sqrt{2p-1} \quad & | \quad \text{square both sides} \\ \left(\dfrac{5}{3}-x\right)^2 &=& 2p-1 \quad & | \quad +1 \\ \left(\dfrac{5}{3}-x\right)^2+1 &=& 2p \quad & | \quad :2 \\ \mathbf{\dfrac{ \left(\dfrac{5}{3}-x\right)^2+1 } {2}} & \mathbf{=}& \mathbf{p} \\ \hline \end{array}\)

 

laugh

 Nov 12, 2018
 #1
avatar+24093 
+10
Best Answer

make "p" the subject.
\(\displaystyle x={5 \over3}- \sqrt{2p-1}\)

 

\(\begin{array}{|rcll|} \hline x &=& \dfrac{5}{3} - \sqrt{2p-1} \quad & | \quad -\dfrac{5}{3} \\ x-\dfrac{5}{3} &=& - \sqrt{2p-1} \quad & | \quad \times(-1) \\ -x+\dfrac{5}{3} &=& \sqrt{2p-1} \\ \dfrac{5}{3}-x &=& \sqrt{2p-1} \quad & | \quad \text{square both sides} \\ \left(\dfrac{5}{3}-x\right)^2 &=& 2p-1 \quad & | \quad +1 \\ \left(\dfrac{5}{3}-x\right)^2+1 &=& 2p \quad & | \quad :2 \\ \mathbf{\dfrac{ \left(\dfrac{5}{3}-x\right)^2+1 } {2}} & \mathbf{=}& \mathbf{p} \\ \hline \end{array}\)

 

laugh

heureka Nov 12, 2018
 #2
avatar+603 
+2

Heureka,

 

Thank you so much for the answer....how daft of me, to multiply the fraction instead of subtracting it...gosh..blush..thank you kindly..

juriemagic  Nov 12, 2018

27 Online Users

avatar
avatar